Analysis of changes in mangrove ecosystems in Banda Aceh city 17 years after the 2004 tsunami - Maulana Gogo; Faisal Abdullah; Saumi Syahreza; Muhammad Budi (Depik, 2022)
Mangrove has the most important role especially in the coastal area. The existence of mangrove habitats in Banda Aceh which got decreasing and loss after tsunami disaster in 2004. The purpose of this study was to the distribution of mangrove in Banda Aceh divided into five (5) sub districts including Jaya Baru, Kuta Alam, KutaRaja, Meuraxa, and Syiah Kuala. This study the mangrove changes after tsunami 2004, began from 2005, 2010, 2015, and 2022. The main data used in this study are Landsat 5 and Sentinel 2A images. Methods of image processing applied in this study are NDVI analysis and supervised classification-based image classification. Theresults are able to show the changes of mangrove area in Banda Aceh from 2004 to 2022. Mangrove area in 2005 is 28.89 ha, 2010 is 81.38 ha, 2015 is 180.27 ha, and 2022 is 121.34 ha. It can be seen that there is a decreasing of mangrove area from 2015 to 2022. The analysis results are also able to show that Kuta raja sub district has the largest mangrove area of 60.11 ha or 49.54 % of the overall area. According to the overall results, it can be said that remote sensing satellite images such as Landsat and Sentinel 2A are very useful in conducting the spatio-temporal research from the long-term periods. This study is hoped to be able to become a reference data in efforts to restore the mangrove in Banda Aceh in order to create the sustainable ecosystem area.Keywords:Mangrove ecosystemsRestorationNDVISupervised classificationSpatio temporal